MiRNA-802 suppresses proliferation and migration of epithelial ovarian cancer cells by targeting YWHAZ - Bo Yang; Li Sun; Lei Liang (BMC, 2019)
Abstract Background The imbalance of expression of microRNA-802 may have a significant place in tumor progression. However, the bio-function of epithelial ovarian cancer cells remains unclear. Therefore, we setup this study to explore the pathogenesis of epithelial ovarian cancer based on microRNA-802. Methods RT-qPCR analysis was used to measure the expression level of microRNA802 and YWHAZ in epithelial ovarian cancer. CCK-8, colony formation, flow cytometry and transwell assay were used to detect the effects of microRNA-802 on cell proliferation, apoptosis, invasion and migration. Target gene prediction and screening, luciferase reporting experiments were applied to validate the downstream target genes of microRNA-802. The effects of microRNA-802 on the expression of YWHAZ and its biological effects were measured by Western blotting and RT-qPCR. Results Compared with normal cell lines and tissues, the expression level of microRNA-802 was obviously down-regulated in cancer related cell lines and tissues. Overexpression of microRNA-802 could obviously inhibit the invasion and proliferation and induce apoptosis. In addition, YWHAZ was the binding target protein of miR-802 for epithelial ovarian cancer cells. YWHAZ was obviously up-regulated in human epithelial ovarian cancer cells, and YWHAZ was negatively correlated with the expression of miR-802. YWHAZ can partly eliminate the inhibitory effect caused by overexpression of miR-802 on growth and metastasis of epithelial ovarian cancer cells. Conclusion miR-802 can regulate the occurrence and development of epithelial ovarian cancer by targeting YWHAZ.